ANALISIS PENALARAN DEDUKTIF SISWA DALAM MENYELESAIKAN MASALAG GEOMETRI BERBASIS ETNOMATEMATIKA - Ni'mah, Dwita Faizatun (IAIN Pontianak, 2025)
Solving mathematical problems with reasoning is still rarely studied. A study needs to be conducted to find out how students think and choose the right steps in solving a problem. This study aims to determine students' deductive reasoning in solving geometry problems based on ethnomathematics in class VIII students of SMP Syarifatul Ulum Katerban. This study uses a qualitative descriptive method. The ethnomathematics-based geometry story test and interview guidelines are the instruments in this study. The data collected were the results of daily geometry test scores, test questions, and interviews. This study was conducted in class VIII of SMP Syarifatul Ulum Katerban. The results of the analysis showed that students with a high score category of 28% were able to meet the deductive reasoning indicators, namely having the ability to construct logical arguments (students are able to understand problems and are able to make plans in solving problems), having the ability to solve problems systematically (students are able to carry out plans by applying correct mathematical concepts), and having the ability to link knowledge with other contexts (students are able to evaluate results and check answers carefully). Students with a medium score category with a percentage of 50% were only able to fulfill the first deductive reasoning indicator, namely the ability to construct logical arguments (students were able to understand problems and were able to make plans to solve problems), and students with a low score category of 22% did not fulfill the deductive reasoning indicator at all.